Kazakhstan : Solid Growth, Unsettled Global Environment - Kazakhstan Economic Update, Fall 2013 - World Bank (World Bank, Washington, DC, 2014)
While the world economy continues to be unsettled, economic growth in Kazakhstan has been solid. Strong domestic demand, coupled with increased oil output and favorable weather conditions, is likely to boost economic growth. An expansion of credit was the key driver of growth in private consumption and investment activity in 2013. Income growth in the country had a positive impact on poverty indicators, with prosperity shared broadly. Prudent macroeconomic policy has helped the economic performance. Prospects of additional oil output with Kashagan coming on stream will help boost economic activity in the coming years and increase Kazakhstan s vulnerability to external shocks unless the country succeeds in diversifying its endowments from natural resources to stronger institutions and higher quality human capital. In his recent speech on the strategic vision Kazakhstan-2050, the President of Kazakhstan highlighted the need to diversify the endowments of the country to achieve its development objectives. He reiterated the key development priorities for the country to become one of the top 30 developed countries by 2050. Trade policy will remain a central instrument to help the country integrate into the global economy, but Kazakhstan will face a complex trade policy environment in the medium-term.